2019
DOI: 10.1017/s0954579418001396
|View full text |Cite
|
Sign up to set email alerts
|

Mother–infant cortisol attunement: Associations with mother–infant attachment disorganization

Abstract: This study explores the conceptualization of mother–infant cortisol attunement both theoretically and empirically, and its association with mother–infant attachment disorganization. In a community sample (N = 256), disorganization and cortisol were assessed during the Strange Situation Procedure (SSP) at infant age 17 months. Salivary cortisol was collected at baseline, and 20 and 40 min after the SSP. We utilized three statistical approaches: correlated growth modeling (probing a simultaneous conceptualizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 70 publications
1
37
0
Order By: Relevance
“…At the same time, there is evidence that dissimilarity in mother and infant cortisol production can be problematic, at least against a backdrop of relatively low demographic risk (i.e., higher socioeconomic status, no history of psychiatric diagnoses). The opposite of attunement-i.e., opposing cortisol difference scores/slopes across a stressor-has been observed in dyads with disorganized attachment (Nofech-Mozes, Jamieson, Gonzalez, & Atkinson, 2020).…”
Section: Physiological Attunement During Stress Depends On Both Rismentioning
confidence: 99%
“…At the same time, there is evidence that dissimilarity in mother and infant cortisol production can be problematic, at least against a backdrop of relatively low demographic risk (i.e., higher socioeconomic status, no history of psychiatric diagnoses). The opposite of attunement-i.e., opposing cortisol difference scores/slopes across a stressor-has been observed in dyads with disorganized attachment (Nofech-Mozes, Jamieson, Gonzalez, & Atkinson, 2020).…”
Section: Physiological Attunement During Stress Depends On Both Rismentioning
confidence: 99%
“…The working definition of synchrony provided above requires that synchrony be directly tied to an interpersonal process – the timescale of which is not yet determined. Some have attempted to investigate this issue by examining multiple different lag times in the same study (e.g., Lunkenheimer et al, 2018a; Nofech-Mozes et al, 2019). Researchers should statistically compare multiple epoch lengths and lag times that make sense for the system being measured (e.g., autonomic activity on the order of seconds, HPA on the order of minutes) and choose the form that best fits the data.…”
Section: Resultsmentioning
confidence: 99%
“…Several primarily large sample studies ( N s = 233–1,141) and two smaller sample studies ( N = 47 and 83) have shown a stronger (or less negative) association between caregiver and infant cortisol reactivity when the caregiver is more positive and responsive and report greater marital satisfaction (Atkinson et al, 2013; Clauss et al, 2018; Hendrix et al, 2018; Hibel et al, 2015; Nofech-Mozes et al, 2019; van Bakel & Riksen-Walraven, 2008). Other studies (with similarly large samples) have found stronger adrenocortical synchrony in dyads from households with higher rates of violence or punitive/intrusive parenting behaviors (Hibel & Mercado, 2019; Hibel et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations